Mucosal IgA response in the colon against pneinnococcal polysaccharide antigen - Marsetyawan HNE Soesatyo, Marsetyawan HNE Soesatyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1994)
The humoral IgA response to bacterial polysaccharide antigen in rats was investigated in vivo. Rats were immunized with pneumococcal polysaccharide type-3 (PPS-3) via different routes, i.e. in the Peyers patch (iPP), in the colon (I.C.), peritoneal cavity (LP.), and intravenous (I.V.). The development of specific antibody-forming cells (AFC) and their isotypes in the intestinal mucosa, gut-associated lymphoid tissue. (GALT), mesenteric lymph nodes (MLN) and spleen were studied by immunohistochemistry. The serum antibody levels were measured by enzyme-linked